Answer:
312 days
Step-by-step explanation:
Number weeks per year is 52
Number of days worked out 6x52 = 312 days
Answer:
pick the answer that explains the graph
Step-by-step explanation:
hope this helps a bit??
Answer:
C.
Step-by-step explanation:
The only thing to do here is just check all of the answers.
A makes no sense, as the number of keys on a keyboard doesn't affect the amount of memory in a computer at all (no correlation).
B makes a bit more sense, but it's still wrong. If a train travels faster, it gets places quicker, or the time goes down. If (If one goes up, the other goes down) is true, then you have negative correlation.
C makes the most sense, as if there's more people at a game, then those more people will probably buy more hot dogs. If (If one goes up, so does the other) is true, then you have positive correlation, which is what we want.
Answer:
See Explanation Below
Step-by-step explanation:
Given
![(sin x - cos x)^2 = sec^2x - tan^2x - 2sinx.cos x.](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20sec%5E2x%20-%20tan%5E2x%20-%202sinx.cos%20x.)
Required
Prove
To start with; we open the bracket on the left hand side
![(sin x - cos x)^2 = (sin x - cos x)(sin x - cos x)](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20%28sin%20x%20-%20cos%20x%29%28sin%20x%20-%20cos%20x%29)
![(sin x - cos x)^2 = (sin x )(sin x - cos x)- (cos x)(sin x - cos x)](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20%28sin%20x%20%29%28sin%20x%20-%20cos%20x%29-%20%28cos%20x%29%28sin%20x%20-%20cos%20x%29)
![(sin x - cos x)^2 = sin^2 x -sinx cos x - sin xcos x + cos^2 x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20sin%5E2%20x%20-sinx%20cos%20x%20-%20sin%20xcos%20x%20%2B%20cos%5E2%20x)
![(sin x - cos x)^2 = sin^2 x -2sinx cos x + cos^2 x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20sin%5E2%20x%20-2sinx%20cos%20x%20%2B%20cos%5E2%20x)
Reorder
![(sin x - cos x)^2 = sin^2 x + cos^2 x - 2sinx cos x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20sin%5E2%20x%20%2B%20cos%5E2%20x%20-%202sinx%20cos%20x)
From trigonometry;
![sin^2x + cos^2x = 1](https://tex.z-dn.net/?f=sin%5E2x%20%2B%20cos%5E2x%20%3D%201)
So;
![(sin x - cos x)^2 = sin^2 x + cos^2 x - 2sinx cos x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20sin%5E2%20x%20%2B%20cos%5E2%20x%20-%202sinx%20cos%20x)
becomes
![(sin x - cos x)^2 = 1 - 2sinx cos x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%201%20-%202sinx%20cos%20x)
Also from trigonometry;
![sec^2x - tan^2x = 1](https://tex.z-dn.net/?f=sec%5E2x%20-%20tan%5E2x%20%3D%201)
So,
![(sin x - cos x)^2 = 1 - 2sinx cos x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%201%20-%202sinx%20cos%20x)
becomes
![(sin x - cos x)^2 = sec^2x - tan^2x - 2sinx cos x](https://tex.z-dn.net/?f=%28sin%20x%20-%20cos%20x%29%5E2%20%3D%20sec%5E2x%20-%20tan%5E2x%20%20-%202sinx%20cos%20x)
Proved